THE INFLUENCE OF LEADERSHIP STYLE, REWARDS, AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT SAMSUNG SERVICE CENTER SURABAYA BRANCH - Waskito Adi, Titok; Ubaidillah, Rizal (Sekolah tinggi ilmu ekonomi pemuda, 2023)
This study aims to test and analyze Leadership Style, Reward, and Work Environment on Employee Performance at the Samsung Service Center Surabaya Branch. Which contains a lack of cooperation between teams and company provisions that are burdensome for employees; thus the thought arises that all these factors are interrelated so that they can affect the performance of employees of the Samsung service center Surabaya branch. This study uses quantitative data by collecting data through employee questionnaires from the Surabaya branch of the Samsung service center as a saturated sample. There are 53 employees who are respondents who are divided into two work divisions: 19 respondents from the operational division and 34 respondents from the technician division. The results of the analysis of this study indicate that partially the variables of Leadership Style, Reward, do not have a significant effect on Employee Performance, while the Work Environment variable significantly affects Employee Performance, the tcount value of each independent variable, namely Leadership Style (X1) is 1.283, Reward (X2) is 1.585, Work environment (X3) is 2.856 and the significance value of each independent variable, namely Leadership Style (X1) is 0.206, Reward (X2) is 0.119, Work environment (X3) is 0.006. However, simultaneously the variables of Leadership Style, Reward, and Work Environment have a significant effect on the Employee Performance variable, the Fcount value is 9.046 with a Ftable value of 2.79 and a significant level of 0.000.